Binocular Diplopia Caused by an Epiretinal Membrane With Foveal Displacement. Issue 1 (March 2020) - Gold, Doria M.; Modi, Yasha S.; Warren, Floyd A.; Rucker, Janet C.
Abstract : Abstract: A 73-year-old woman presented with 3 years of monocular visual distortion and progressive binocular diplopia. She was found to have a comitant left hypertropia due to an epiretinal membrane causing inferior foveal drag. Displacement of the fovea from an epiretinal membrane is a likely under-recognized cause ocular cause of a comitant binocular diplopia.